Valorization of Urtica dioica roots as a highly-effective and eco-friendly biosorbent for adsorptive removal of hazardous textile dyes - Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (ELSEVIER, 2023)
In this study, Urtica dioica roots were used in the biosorption of CR and SO dyes for the first time. FTIR-ATR, SEM, and BET were applied to characterize the biosorbent. The isotherm, kinetic, thermodynamic, and error analyses were investigated. Langmuir isotherm was found to be the most feasible for biosorption according to the highest r2. The qm for CR and SO dyes were calculated from the Langmuir model as 417 and 625 mg/g at 25 degrees C, respectively. It was found that the removal of CR and SO followed the PSO model. Besides, it was determined that the biosorption process from the IPD occurred in three stages. Negative values of & UDelta;Go and & UDelta;Ho confirmed that the biosorption was spontaneous and exothermic. All results illustrated that biosorbent can be used as an ecofriendly, low-cost, and reusable biosorbent in the scope of zero waste in the removal of different textile dyes from wastewater.
Keywords: Urtica dioica roots; Safranine O; Congo Red; Biosorption; Statistical analysis; METHYLENE-BLUE DYE; CONGO RED-DYE; WASTE-WATER; AQUEOUS-SOLUTION; REACTIVE DYE; ENHANCED ADSORPTION; MALACHITE GREEN; NANOCOMPOSITE; OPTIMIZATION; EQUILIBRIUM; Materials Science; Physics